Application of Wetland-Based Entrepreneurship Orientation and Entrepreneurial Competence to Increase MSME Income in Wetlands - Anisah, Hastin Umi; Isnawati; Rifqi Novriyandana; Muchammad Yusup (Open Access Indonesia Journal of Social Sciences, 2021)
This study aims to determine and analyze the application of wetland-based entrepreneurial orientation and entrepreneurial competence to increase MSME income. With the increase in the income of MSMEs, it is expected to improve the welfare of MSMEs. Quantitative research method used in this research with PLS analysis technique. As for the long term, MSME actors, in this case "Nipah Leaf" craftsmen, can have entrepreneurial competence so that they can increase the income of MSME actors. The expected result is an academic justification for the role of wetland-based entrepreneurial orientation and entrepreneurial competence in increasing MSME income. The results of this study are expected to be a policy consideration taken by the South Kalimantan Regional Government as a program to increase MSME income. The results of the research are also expected to be able to advocate for the craftsmen of "Daun Nipah" to have an entrepreneurial orientation based on wetlands and entrepreneurial competence.